Review of the Accuracy of Codification of Chronic Kidney Disease Cases Based on ICD-10 at Hospital X in 2023 - susanah, Susanah; Aryani, Bhakti; Haryanto, Yanto; Dewi Rahmawati, Fitria (LPPM Universitas Dhyana Pura, 2025)
Chronic Kidney Disease is an irreversible kidney disease, with abnormalities in kidney structure and function. Based on the BPJS Health report, the number of catastrophic disease sufferers in Indonesia will increase to around 29.7 million cases by 2023. Kidney failure disease ranks 4th, with an increase in cases from 1.3 million to 1.5 million cases with treatment costs of IDR 2.9 trillion. The accuracy of diagnosis coding based on ICD-10 is very important for the quality of hospital services, reporting, and the accuracy of health insurance claim rates. In 2023 chronic kidney disease at hospital X as many as 229 medical records of inpatients who have performed hemodialysis. This study aims to assess the accuracy of diagnosis coding of chronic kidney disease cases based on ICD-10 at hospital X in 2023. This study used a quantitative descriptive method with a sample size of 146 medical records of inpatients, using random sampling techniques. Data collection techniques in this study were carried out by means of observation of medical record documents, Data analysis in this study is a univariate analysis carried out by the formula, category frequency: total sample x 100%. From the results of the percentage calculation, it shows that the accuracy of the chronic kidney disease diagnosis code is 112 cases (77%) and 34 cases (23%) are inaccurate. The inaccuracy was due to coder errors in determining the combination code, incomplete medical information, and coder accuracy in analyzing medical record documents.